Choosing a faith school in Leicester: admissions criteria, diversity and choice - Levitt, Mairi (British Journal of religious education, 2020)
Religion in Britain is in overall decline and no religion' is growing, but one-third of schools in the State sector in England and Wales are schools with a religious designation' (faith schools'). Historically, these were Protestant and Catholic Church schools, but new faith schools have been established by Churches and other faiths. Governments of all parties have encouraged this development, chiefly on the grounds of increased parental choice and improved quality.The research presented here provides evidence about the operation of faith schools in the English city of Leicester in 2016, particularly from the perspective of those choosing a school. The main objectives are (1) to indicate the diversity of faith schools, (2) to show how they present themselves to those looking for a school: their admission requirements and level of educational attainment and (3) to reflect on the claim that faith schooling offers more and better choice and quality. Leicester is selected for its size and diversity; it is small enough to study with the resources available to us and is one of the most multi-ethnic and multifaith urban areas in England. Research was carried out between February and July 2016 and offers a snapshot from that year.